Corona pandemic: awareness of health care providers in Pakistan - Sadia Minhas; Rabia Mushtaq Chaudhry; Aneequa Sajjad; Iram Manzoor; Atika Masood; Muhammad Kashif (AIMS Press, 2020)
Introduction: Corona pandemic has resulted in a high mortality rate among health care professionals. The purpose of this study was to assess the knowledge and practices of health care providers during this pandemic in Punjab, Pakistan. Methods: A web based cross sectional survey was conducted during 2nd of April to 20th April 2020 targeting health care professionals working in Punjab, Pakistan. A sample of 540 participants was collected using non probability, convenient sampling technique. Data was generated by using on line google forms after taking IRB approval from institution. Results: Adequate knowledge was found among health care providers regarding diagnostic tests, modes of transmission, incubation period and preventive strategies. Significant association was seen in knowledge of post graduate and MBBS doctors (Bachelor of Medicine and Bachelor of Surgery) regarding viral etiology (p = 0.006), sign and symptoms (p = 0.000), risk factors (p = 0.000) and mortality rates (p = 0.001). Hand washing was considered as best preventive measure by 95% of the health care providers. Conclusion: Post graduate doctors have better knowledge regarding corona virus disease transmission, risk factors, incubation period and preventive strategies as compared to undergraduate doctors.